708 A NEW DIAGNOSTIC PARADIGM FOR LARYNGOPHARYNGEAL REFLUX DISEASE: CORRELATION OF IMPEDANCE-PH MONITORING AND DIGITAL REFLUX SCINTIGRAPHY RESULTS. (17th September 2021) - Park, Jin-soo; Khoma, Oleksandr; Van Der Wall, Hans; Falk, Gregory
Abstract: : No gold-standard investigation exists for laryngopharyngeal reflux (LPR). Multichannel intraluminal impedance (MII)-pH testing has uncertain utility in LPR. Meanwhile, reflux scintigraphy allows immediate and delayed visualisation of tracer reflux in the esophagus, pharynx, and lungs. The present study aimed to correlate MII-pH and scintigraphic reflux results in patients with primary LPR. Methods: Consecutive patients with LPR underwent MII-pH and scintigraphic reflux studies. Abnormal values for MII-pH results were defined from existing literature. MII-pH and scintigraphic data were correlated. Results: 105 patients with LPR (31 males (29.5%), median age 60 years (range: 20–87)) were studied. Scintigraphic reflux was seen in the pharynx in 94 (90.4%), and in the proximal esophagus in 94 (90.4%). Delayed scintigraphic contamination of the pharynx was seen in 101 patients (96.2%) and in the lungs of 56 patients (53.3%). Abnormal reflux was seen in the distal esophagus in 12.4%, proximal esophagus in 25.7%, and in the pharynx in 82.9%. Patients with poor scintigraphic clearance had higher Demeester scores (p = 0.043), more proximal reflux episodes (p = 0.046), more distal acid reflux episodes (p = 0.023), and longer bolus clearance times (p = 0.002). Conclusion: Reflux scintigraphy has a high yield in LPR patients. Scintigraphic time-activity curves correlated with validated MII-pH results. A high rate of pulmonary microaspiration was found in LPR patients. This study demonstrated a high level of pharyngeal contamination by scintigraphy and MII-pH, which supports the use of digital reflux scintigraphy in diagnosing LPR.